Molecular Epidemiology of Carbapenem-Resistant Klebsiella pneumoniae in a Tertiary Hospital in Northern China - Shuqing Wang; Huanhuan Dong; Meiqi Wang; Wenbo Ma; Yue Cheng; Junliang Zhou; Yongming Cheng; Hui Xu; Xiaochen Yu (Canadian Journal of Infectious Diseases and Medical Microbiology)
Background. In recent years, carbapenem-resistant Klebsiella pneumoniae (CRKP) has emerged rapidly in China with the abuse and overuse of antibiotics, and infections caused by CRKP pose a serious threat to global public health safety. The present study aimed to explore the epidemiological characteristics of CRKP isolates in Northern China and to elucidate their drug resistance mechanisms. Methods. 45 CRKP strains were consecutively collected at a teaching hospital from March 1st, 2018 to June 30th, 2018. Antimicrobial susceptibility was determined by the VITEK2 compact system and microbroth dilution method. Polymerase chain reaction (PCR) and sequencing were used to analyze multilocus sequence typing (MLST), drug resistance determinants, and plasmid types. The transfer of resistance genes was determined by conjugation. All statistical analysis was performed using SPSS 22.0 software. Results. All 45 isolates showed multidrug resistance (MDR). MLST analysis showed ST11 (48.9%, 22/45) was the most frequent type. All of the 45 CRKP isolates contained carbapenemase genes, extended-spectrum β-lactamase (ESBL) genes, and plasmid-mediated quinolone resistance (PMQR) genes. For carbapenemase genes, KPC-2 (93.3%, 42/45) was the main genotype, and followed by GES (37.8%, 17/45) and NDM-1 (11.1%, 5/45). Plasmid typing analysis showed that IncFII and IncFIB were the most prevalent plasmids. The carbapenem resistance rate of K.pneumoniae was 11.4% and ICU was the main CRKP infection source. Conclusions. ST11 is the most frequent sequence type and KPC-2 is the predominant carbapenemase of CRKP strains in Northern China. KPC-2-ST11 are representative clonal lineages.